Utilization of marine taxa within an artisanal shellcraft sector of the Indo-Pacific region - Simard, Nittya S. M.; Militz, Thane A.; Kinch, Jeff; Southgate, Paul C. (Frontiers in Marine Science, 2022)
Sustainable utilization of marine taxa is critical for maximizing social and economic goals of livelihood development within the Indo-Pacific. Yet, despite an increasing importance of shellcraft as a livelihood activity within the Indo-Pacific, information on the taxa utilized within shellcraft sectors remains scant. To address this knowledge gap, our study examined diversity, in terms of composition and quantities, of marine taxa utilized by artisan households and, collectively, within an artisanal shellcraft sector of Papua New Guinea. For each taxon, critical source habitats were identified, and the geographic scale of exploitation established. Critically, presented data revealed 73 taxa, representing at least 77 species, were utilized within the studied sector. Many of the taxa utilized had not previously been linked to shellcraft sectors, demonstrating that a broader composition of taxa is utilized than previously acknowledged. In terms of quantity, annual utilization within the sector was close to 500,000 individuals, the majority being mollusks of either class Gastropoda (83.6%), represented by 37 genera, or class Bivalvia (9.6%), represented by four genera. There was a strong bias towards a particular species, Chrysostoma paradoxum (78.5% of all individuals), as indicated by indices for the diversity utilized (H′ = 1.23; D = 0.38). However, substantial variation was evident in the diversity of taxa utilized among households (n = 36) engaged in shellcraft (H′ = 1.09 ± 0.71; D = 0.43 ± 0.27), with each household utilizing a unique composition of 19.1 ± 10.6 taxa. Source habitats for taxa ranged from pelagic to benthic intertidal and subtidal substrates, with the geographic scale of exploitation extending to 34 discrete locations up to 417 km away. The array of sector, household, and taxon-specific information presented provides a basis for supporting greater sustainability within shellcraft sectors across the Indo-Pacific, which is discussed within a context of informing community-based resource management, further developing marine aquaculture, and strengthening existing governance.